Firm-level investment under imperfect capital markets in Ukraine - Oleksandr Shcherbakov (Bank of Canada, 2019)
This paper develops and estimates a model of firm-level fixed capital investment when firms face borrowing constraints. Dynamically optimal investment functions are derived for the firms with and without financial constraints. These policy functions are then used to construct the likelihood of observing each of the investment regimes in the data. Structural parameters are estimated using data from the Ukrainian manufacturing sector in 1993-1998. I provide empirical evidence of the role of market and ownership structure for firm-level investment behavior. I also discuss the effects of international trade exposure and involvement in non-monetary transactions on the probability of facing financial constraints and the resulting fixed capital accumulation path. Estimation results are used to illustrate the welfare implications of financial constraints in the Ukrainian manufacturing sector.
Keywords: C61; C63; D24; G31; 330; Econometric and statistical methods; Economic models; Firm dynamics